2017
DOI: 10.1002/ijc.30643
|View full text |Cite
|
Sign up to set email alerts
|

Secondary bile acid-induced dysbiosis promotes intestinal carcinogenesis

Abstract: The gut microbiota plays an important role in maintaining intestinal homeostasis. Dysbiosis is associated with intestinal tumorigenesis. Deoxycholic acid (DCA), a secondary bile acid increased by a western diet, correlates with intestinal carcinogenesis. However, evidence relating bile acids, intestinal microbiota and tumorigenesis are limited. In our study, we investigated the effect of DCA on induction of intestinal dysbiosis and its roles in intestinal carcinogenesis. Alteration of the composition of the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
142
3
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 184 publications
(160 citation statements)
references
References 51 publications
6
142
3
1
Order By: Relevance
“…Importantly, in most experimental studies the increased fecal bile acid levels alone were not sufficient to induce intestinal tumor formation, but required increased susceptibility of the rodent model mediated by chemical treatment or genetic disposition [23, 24, 27•, 29]. One study found an inherent tumor-inducing effect for DCA in wild-type mice when this secondary bile acid was added to the diet [25], but tumor formation was only observed after a comparatively long time frame (8–10 months).…”
Section: Bile Acids Act As Tumor Promotersmentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, in most experimental studies the increased fecal bile acid levels alone were not sufficient to induce intestinal tumor formation, but required increased susceptibility of the rodent model mediated by chemical treatment or genetic disposition [23, 24, 27•, 29]. One study found an inherent tumor-inducing effect for DCA in wild-type mice when this secondary bile acid was added to the diet [25], but tumor formation was only observed after a comparatively long time frame (8–10 months).…”
Section: Bile Acids Act As Tumor Promotersmentioning
confidence: 99%
“…Similarly, lower fecal levels of CA observed in cirrhosis patients coincided with reduced abundance of 7α-dehydroxylating bacteria in the feces [33]. In contrast, a recent study detected different compositional shifts of the gut microbiota after adding DCA to the diet of Apc min+ mice [29]: at phylum level, the administration of DCA triggered an increased abundance of Bacteroidetes and decreased numbers of Firmicutes compared to Apc min+ mice that received a diet without additional DCA. However, this may be not surprising, since DCA was shown to have more potent antimicrobial activity than CA [36] and Apc min+ mice are likely to have an altered gut microbiota compared to wild-type mice.…”
Section: Bile Acids Alter Gut Microbiota Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, IEC-derived SIRT1, a NAD+-dependent protein deacetylase downregulated in UC patients, prevents age-dependent reduction of Bacilli/ Lactobacillus partially via regulating bile acid metabolism (29). In addition, DCA administration accelerates tumorigenesis by inducing microbiota dysbiosis and inflammation in Apc min/+ mice (30*). Fecal transfer of DCA-treated but not untreated Apc min/+ mice induced low grade inflammation and activated M2 tumor-associated macrophages and the WNT/β-catenin pathway in recipient Apc min/+ mice (30*).…”
Section: Metabolismmentioning
confidence: 99%
“…In addition, DCA administration accelerates tumorigenesis by inducing microbiota dysbiosis and inflammation in Apc min/+ mice (30*). Fecal transfer of DCA-treated but not untreated Apc min/+ mice induced low grade inflammation and activated M2 tumor-associated macrophages and the WNT/β-catenin pathway in recipient Apc min/+ mice (30*). …”
Section: Metabolismmentioning
confidence: 99%